Clinical profile of acute hemorrhagic stroke patients: a study in tertiary care hospital in Northern India - Baidya, Omkar P.; Tiwari, Sunita; Usman, Kauser (International Journal of Research in Medical Sciences, 2017)
Background: Acute hemorrhagic stroke, a subtype of acute stroke is one of the leading cause of death and major cause of morbidity and mortality throughout the world. The incidence of acute hemorrhagic stroke is increasing with gradual increase in obesity, diabetes mellitus, hyperlipidemia, hypertension and various cardiac problems. This study had been conducted with an objective to study the risk factors and clinical presentation of acute hemorrhagic stroke patients in north-Indian population. Methods: This study was carried out among 100 acute hemorrhagic stroke patients (clinically and radiologically confirmed) irrespective of age and sex admitted to Emergency Department of KGMU, Lucknow after getting clearance from Institutional Ethical Committee(IEC). These patients had been subjected to plane CT (computed tomography) scan brain on admission by the CT scan model 16 slice Brivo 385 for radiological confirmation and to localize the lesion in brain. Data were collected in prescribed protocol. Results: Majority of the patients were in the (50-60) age group with male predominance. Hypertension (62%) was the most common risk factor for acute hemorrhagic stroke followed by Non-veg diet (46%). The commonest clinical feature at presentation was hemiplegia (76%). Majority (47%) of the patients presented with Glasgow Coma Scale (GCS) of (9-12). Cerebral cortex (41%) was the most common site of brain lesion in acute hemorrhagic stroke patients. Conclusion: This study focuses on the clinical profile and risk factors of acute hemorrhagic stroke, by targeting which the burden of this disabling disease can be prevented.